Richard Francis Burton e a inserção do kama-sutras como um manual sexual entre os vitorianos (Inglaterra, 1883) - Weissheimer, Felipe Salvador (2014)
Amongst the various Kama-sutras published in the market, the classical version was written by Vatsyayana (I-IV centuries, approximately) and published in England in 1883 by the Kama-Shastra Hindu Society. Richard Francis Burton was the member with most importance in the Kama-Shastra Hindu Society, given that he not only fomented the publication, but also helped with the translation, edited and uttered several comments during the work. In his comments, we can notice how the project of translation and publication of the Kama-sutras pointed specially towards the institution of new sexual practices to his contemporaries. For him, mattered not only to know the other , but also to learn with the other , and the discourse of Vatsyayana was built by him in this learning manual . From the Kama-sutras, Burton imagined an exotic East , carrier of sexual and erotic knowledge. This imagined community by the translator-commentator created a discursive effect of considerable stimulus over the affective dispositions of the readers, fact that reinforced his ideological action of Victorian erotic and sexual practices transformation. Burton thought that the Kama-sutras was important for Englishmen, for it contained many new and interesting things about the union of sexes . Moreover, he observed that the ignorance about sex led Englishmen to not fully enjoy marital delights, as well as not completely satisfying the sexual desires of their wives. Thus, we notice that there was an immanent sense in the discourse of Burton about Indian past, in which the translator-commentator sought for the intent of reaching the truth about Indian past, strike English reality at the end of the 19th century. In the analysis of the extracts from those involved in the translation and publication of Kama-sutras, there can be seen, for instance, the existence of legal interdictions, such as those promulgated by the Obscene Publications Act of 1857, which regulated the publications of an erotic and sexual sort. Besides, after a historiographical review and taking the reports of those involved in the production of the Kama-sutras as a source, we have seen that the conflicts between the producers of the Kama-sutras and the guardians of chastity (who fought the so called obscene publications ) happened, above all, in the bosom of the bourgeois class, even if it was not an exclusively bourgeois conflict. In this sense, we analyze (not only the English translation of the Kama-sutra, but also other texts that were at the tangle of relationships interdiscursive), the representations, interventions and disciplines, social and culturally constructed in England in the late nineteenth century, that focused on bodies and on the identities of the Victorians